Sudden Visual Loss After Vitreoretinal Surgery: A Case Report - Agostino Salvatore Vaiano; Fabio Garavelli; Antonio Greco; Riccardo Merli; Alessandro De Filippis; Andrea Greco; Maria Marenco (Case Reports in Ophthalmological Medicine)
A 51-year-old male underwent vitrectomy with retrobulbar anesthesia for retinal detachment. Post surgery, he experienced systemic hypotension which normalized after 3 h. The day after, he complained of a central scotoma in the operated eye. Intraocular pressure was normal, but fundus examination revealed hemorrhages and whitening along the papillomacular bundle and macula, with additional whitening in the upper midperipheral region. Multimodal imaging confirmed branch retinal vein, artery, and cilioretinal artery occlusion. Further examination revealed mild-to-moderate obstructive sleep apnea syndrome. Vascular occlusions are potential complications of vitreoretinal surgery, warranting thorough preoperative assessment for underlying risk factors, even if causative mechanism is still unknown.